2009
DOI: 10.1002/ps.1782
|View full text |Cite
|
Sign up to set email alerts
|

Attraction and antennal response of the common wasp, Vespula vulgaris (L.), to selected synthetic chemicals in New Zealand beech forests

Abstract: These results are the first to be reported on the EAG response and the attraction of social wasps to synthetic chemicals in New Zealand beech forests and will enable monitoring of social wasp activity in beech forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…This is particularly interesting considering that most of the literature on Vespula spp. management options are related to the use of attractive baits, and most studies are conducted in the field with traps baited with different lures (Davis et al 1972;Landolt 1998;Day & Jeanne 2001;El-Sayed et al 2009). It could be more cost-effective in such cases where the aim is to identify attractive compounds to use a wind tunnel or laboratory bioassay (Boevé et al 2014) to screen for potential active compounds before conducting a field study.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly interesting considering that most of the literature on Vespula spp. management options are related to the use of attractive baits, and most studies are conducted in the field with traps baited with different lures (Davis et al 1972;Landolt 1998;Day & Jeanne 2001;El-Sayed et al 2009). It could be more cost-effective in such cases where the aim is to identify attractive compounds to use a wind tunnel or laboratory bioassay (Boevé et al 2014) to screen for potential active compounds before conducting a field study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, traps baited with sweet beer to target Vespa velutina killed numerous other insects, notably Vespula vulgaris, Vespa crabro and various Diptera and Lepidoptera (Dauphin and Thomas 2009;Rome et al 2011). A number of synthetic compounds have been shown to be attractive to social wasps, including heptyl butyrate (Davis et al 1969;El-Sayed et al 2009;Landolt 1998b), 2,4-hexadienyl butyrate (Davis et al 1967), and a mixture of acetic acid with saturated short chain alcohols (Landolt 1998a;Landolt et al 2000). Although attracting and trapping adults can capture a large number of adults, there seems to be enough redundancy of adults within each colony that this results in surprisingly minimal effect on the colony.…”
Section: Management Optionsmentioning
confidence: 98%
“…While such antagonistic interactions are rare, some are reported in the literature. For instance, the addition of acetic acid to HB blocked its ability to lure V. vulgaris and V. germanica into traps in New Zealand [22]. However, this combination previously showed synergy in attracting V. germanica to traps in other tests [12].…”
Section: Discussionmentioning
confidence: 99%
“…Others have hypothesized that a similar interaction occurs between honeydew volatiles and isobutanol in New Zealand beech forest [7]. That is, while some studies have shown isobutanol to be effective at trapping V. vulgaris in both Europe and New Zealand [7,24], tests conducted in a beech forest that is rich in honeydew have shown no response [22]. This discrepancy may be due to high background levels of honeydew volatiles that antagonize the attractiveness of other compounds by overwhelming or re-directing the wasp olfactory system to a more abundant food source.…”
Section: Discussionmentioning
confidence: 99%